(untitled) (Cardiovascular Journal, 2016)
Background: Hypertension is an important public-health challenge worldwide. It is important because of its high frequency and its effect on cerebrovascular, cardiovascular and kidney disease. Methods: This cross-sectional descriptive study was conducted to assess the treatment compliance of hypertensive patients and medical history of patients with hypertension in the outpatient department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka. Considering inclusion and exclusion criteria, 350 hypertensive outdoor patients were included in this study. Data was analyzed by SPSS version 20. Results: The study revealed that the mean age of the respondents was 50.49 years (SD ± 8.449). Approximately 67.2% of the respondents were suffering from hypertension from <5 years and 15.6% respondents were hospitalized three times and 12.0% respondents were hospitalized more than three times. The mean duration of taking antihypertensive medicine was 4.91 years. The study also found that 48.8% respondents were taking antihypertensive medication irregularly. The mean systolic blood pressure was 129.96 mm of Hg (SD±23.60) and diastolic blood pressure was 86.08 mm of Hg (SD ±12.76). Conclusion: The study results revealed that about half of the patients do not take drugs regularly, which is an alarming sign. Therefore, the instructions and counseling should be given to the patient to fulfill the treatment for prevention of complications related to hypertension. Cardiovasc. j. 2016; 8(2): 110-114